(untitled) (Management and Connections Journal, 2023)
Anti-consumption has been growing among consumers in different cultures, such as emerging countries in Latin America. Such countries have underdeveloped economies and great social inequality, which makes it pertinent to investigate the relationship between the individual’s social class and the adoption of anti-consumption, mediated by life satisfaction, financial well-being, and materialism. A descriptive, quantitative and single-cut study was used. Data from Latinobarómetro (2017), with a sample of 17,608 individuals, were used to employ a multivariate mediation analysis. The results show that more satisfied individuals with better financial well-being are more likely to adopt the consumption reduction movement. On the other hand, materialism decreases the propensity to adopt anti-consumption. These results contribute to highlighting some determinants that impact the lifestyle of consumption reduction in emerging countries.